2020
DOI: 10.3390/su12198122
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Water-Use Efficiency and the Agricultural Productivity: An Application Case in a Modernized Semiarid Region in North-Central Mexico

Abstract: The increasing population demands a greater quantity of food. In order to satisfy the world’s demand, one of the main challenges worldwide consists of modernizing the current irrigation systems. This research shows an experience carried out in a modernized irrigation module in Central-North Mexico following these objectives: to evaluate the impact of the modernization of the irrigation module, to analyze the agricultural productivity, and to assess a group of parameters related with the agricultural production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Agricultural activity consumes 70% of the water withdrawn in the world and it is expected that competition for water resources in this area will increase soon [1]. The use of water-optimizing irrigation techniques is essential to achieve sustainable agriculture, especially in arid and semiarid regions [2].…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural activity consumes 70% of the water withdrawn in the world and it is expected that competition for water resources in this area will increase soon [1]. The use of water-optimizing irrigation techniques is essential to achieve sustainable agriculture, especially in arid and semiarid regions [2].…”
Section: Introductionmentioning
confidence: 99%
“…As the main body of economic and social development, the demographic factor is the fundamental factor driving changes in water consumption, and there is a high degree of consistency between total water consumption and per capita water consumption (Figure 1). At present, water resources have become the main indicator to measure the regional population carrying capacity [1]. With the change of China's population structure, a comprehensive study of the relationship between the change of population structure and water consumption will be conducive to exercising the green development concept of harmony between people and water, as well as the ecological civilization construction, and also help to further promote economic and social sustainable development.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, micro-level studies have been conducted based on the above theory; Hu Zhen et al argue that the impact of household size on water consumption showed an inverted "N" trend, and in the age structure of population, the order of influence degree of water consumption was middle-aged > minors > the elderly > young adults [25]. Tong Yufen and Li Zheng [1] further analyzed water consumption according to the income level of residents. Simultaneously, some scholars also analyzed the impact of population structure on water consumption at micro-levels, such as the urban and rural population ratio, diet structure, education level, and Engel coefficient [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The modernization of hydro-agricultural infrastructure and the application of more efficient irrigation systems are actions that are being applied in several countries of the world to increase irrigation efficiency and improve water management. González-Trinidad et al [ 2 ] evaluated water efficiency and agricultural productivity in a modernized semi-arid region in central-north Mexico. Their results indicated a 30% increase in global efficiency and higher yields in all crops.…”
Section: Introductionmentioning
confidence: 99%
“…Model trained with 86 characteristics to classify five phenological stages 2. model trained with 45 characteristics to classify five phenological stages.…”
mentioning
confidence: 99%